A Clinical Device for Measuring Internal-External Rotational Laxity of the Knee. (January 2013) - Alam, Mahbub; Bull, Anthony M.J.; Thomas, Rhidian deW; Amis, Andrew A.
Background: The dial test can be improved by providing reproducible, accurate measurements to improve diagnosis and treatment comparisons. Purpose: Validation of a rotational measurement device (RMD) for measuring knee internal-external rotational laxity. Study Design: Cohort study (diagnosis); Level of evidence, 2. Methods: The RMD consisted of 3 components: a femoral clamp and a tibial splint using paired inclinometers to measure rotations, and a boot to apply tibial internal-external rotation torque. A separate boot inclinometer allowed for foot rotations to be measured independently. The measurements were simultaneously compared with electromagnetic "nest of birds" (NOB) sensors. Sequential paired knee measurements were taken at 4, 6, and 8 N·m of torque at 30° and 90° of flexion in 46 volunteers. Results: The correlation coefficient was 0.92 (95% CI, 0.89 to 0.94) and 0.63 (95% CI, 0.54 to 0.70) between the NOB and RMD and between the NOB and boot inclinometer, respectively. Bland-Altman analysis revealed that the RMD was on average within 2° (95% CI, 1° to −4°) of NOB readings, whereas the boot overestimated by 34° (95% CI, −9° to −58°). Maximum side-to-side differences measured by the NOB, RMD, and boot were 1°, 3°, and 21°, respectively. The mean +2× standard deviation data gave a range of side-to-side differences of less than 5° for the RMD. The intraobserver intraclass correlation was 0.9 (95% CI, 0.78 to 0.97) at both 30° and 90° of flexion, and the 95% CI of the differences between readings taken on 2 occasions, the interobserver repeatability, was 1° or less. Conclusion: The novel clinical RMD for measuring rotational laxity of the knee was portable, easy, and comfortable to use in the clinical setting. The RMD showed significant correlation and accuracy compared with sensors of known high accuracy. Side-to-side differences of less than 5° were found in 95% of normal knees, compared with differences of 13° or more for clinical diagnosis of pathological rotational laxity. Measuring knee rotation at the foot showed poor correlation and accuracy.